Experimental and Numerical Investigation of Concrete-Filled Tube Beams: A Review Paper (Journal of Engineering, 2025)
Concrete-filled steel tubes (CFST) are structural members consisting of hollow steel tubes filled with concrete. Both steel and concrete work together to provide several advantages. The concrete increases the steel tube's resistance against local buckling while the steel tube confines the concrete, which increases its compressive strength. The use of CFST beams increased in high buildings due to their great mechanical properties. The researchers were interested in CFST beams because of their great ductility, stiffness, strength, and flexural capacity when compared to hollow steel beams. The properties of CFST beams were enhanced in several ways, for example, by using carbon fiber reinforced polymer (CFRP) wrapping, adding an external steel plate, and using recycled aggregate. In addition, the concrete properties were improved by adding steel and synthetic fibers. This review paper covers research conducted on CFST beams since 2019. It gives an overview of what was studied and explored and what still needs more research.